Computational modeling predicts the ionic mechanism of late-onset responses in unipolar brush cells - Subramaniyam, Sathyaa; Solinas, Sergio; Perin, Paola; Locatelli, Francesca; Masetto, Sergio; D'Angelo, Egidio (Frontiers in Cellular Neuroscience, 2014)
Unipolar Brush Cells (UBCs) have been suggested to have a strong impact on cerebellar granular layer functioning, yet the corresponding cellular mechanisms remain poorly understood. UBCs have recently been reported to generate, in addition to early-onset glutamatergic synaptic responses, a late-onset response (LOR) composed of a slow depolarizing ramp followed by a spike burst (Locatelli et al., 2013). The LOR activates as a consequence of synaptic activity and involves an intracellular cascade modulating H- and TRP-current gating. In order to assess the LOR mechanisms, we have developed a UBC multi-compartmental model (including soma, dendrite, initial segment and axon) incorporating biologically realistic representations of ionic currents and a generic coupling mechanism regulating TRP and H channel gating. The model finely reproduced UBC responses to current injection, including a low-threshold spike sustained by CaLVA currents, a persistent discharge sustained by CaHVA currents, and a rebound burst following hyperpolarization sustained by H- and CaLVA-currents. Moreover, the model predicted that H- and TRP-current regulation was necessary and sufficient to generate the LOR and its dependence on the intensity and duration of mossy fiber activity. Therefore, the model showed that, using a basic set of ionic channels, UBCs generate a rich repertoire of delayed bursts, which could take part to the formation of tunable delay-lines in the local microcircuit.